Harina de camote morado combinado con Lactobacillus Plantarum como factores mitigantes de gases invernaderos en cerdos durante la etapa de engorde - Barre Mendoza, Jhon Erick (2025)
Pig production is one of the main sources of greenhouse gas (GHG) emissions. This study evaluated the impact of including purple sweet potato (Ipomoea batatas L.) and probiotics (Lactobacillus plantarum) in pig diets to mitigate GHG emissions, specifically carbon dioxide (CO₂) and ammonia (NH₃). Thirty-six male pigs were used, distributed across nine dietary treatments combining different proportions of protein concentrate plus corn, purple sweet potato, and Lactobacillus. CO₂ and NH₃ emissions were measured over 49 days using a gas detector. The results showed that treatments including purple sweet potato and probiotics significantly reduced CO₂ and NH₃ emissions. The most effective treatment combined 40% purple sweet potato with 40 ml of Lactobacillus, achieving a significant decrease in CO₂ emissions (1270 ppm) and NH₃ emissions (24.5 ppm). Statistical tests (Kruskal-Wallis and Wilcoxon) confirmed significant differences (P ≤ 0.001) among treatments for both variables. In conclusion, the addition of purple sweet potato and probiotics to pig diets is a promising strategy for reducing GHG emissions, contributing to environmental sustainability without compromising pigs’ productive performance.